Modernization in Israeli Arab Society – Parent Intervention Prog - Salah Abo Ganim, Sondos Ali (Studia Edukacyjne, 2019)
The main objective of this article to review the advantages and effectiveness of the parental intervention program based on the conceptual model, in which the parents are agents of change in the raising of the awareness and the increase of the knowledge about the developmental changes during adolescence and the reinforcement of the authoritative parenting style, and to examine whether the proposed parental intervention will lead to the promotion of health behaviors, including the improvement of sleep patterns, the limitation of the exposure to media, and the improvement of the quality of life among Arab adolescents.